Profiling of mono- and diglyceride from edible fats by GC×GC-TOF-MS for halal authentication - Indrasti, Dias; Chin, Sung Tong; Che Man, Yaakob; Mustafa, Shuhaimi; Mat Hashim, Dzulkifly (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Production practice of mono- and diglycerides (MG-DG) compound, as emulsifying agent, involves interesterification of glycerines with triglycerides (TG) derived from plant or animal or through enzymatic process. Analysis of MG-DG mixtures using GC×GC technique coupled to time-of-flight mass spectrometry (TOF-MS) of three different oils of lard (LA), palm (PA) and butter (BU) remains a challenging prospect for tracking the TG source in the study of Halal authentication. The results show that PA and LA have similar compositions in terms of concentrations of MG-DG contents. However, compared to PA, LA contains much more of MG C18. BU is discriminated on its content of MG C10, MG C14, DG 1,3-C14, and DG 1,3-C16.